Multiscale microstructural heterogeneity and mechanical property scatter in Inconel 718 produced by directed energy deposition - Yeoh, Yong Chen (2021)
Directed energy deposition (DED) is an additive manufacturing technique that enables rapid production and repair of metallic parts with flexible geometry. The complex nature of thermal and material transport during DED can yield unwanted microstructure heterogeneity, which causes scatter in parts performance. Here, we investigate microstructure variations at different length scales in Inconel 718 produced by powder-blown DED using different deposition rates. We quantify spatial trends in grain structure, texture, composition, and solidification structure within parts and correlate them with variations in hardness, yield strength, and Young's Modulus to highlight the effect of the thermal environment during solidification. We find that the high energy input employed when using high deposition rates is conducive to significant microstructure heterogeneity along both the build and transversal directions, which stems from the asymmetric cooling rates generated by the deposition strategy used. We also find that standard heat treatments employed on Inconel 718 are not suitable to homogenize the microstructure. These results have important implications for the development of industrially relevant build rate strategies for additively manufactured parts.